The outer membrane porin OmpW of Acinetobacter baumannii is involved in iron uptake and colistin binding. Issue 2 (11th January 2016) - Catel‐Ferreira, Manuella; Marti, Sara; Guillon, Laurent; Jara, Luis; Coadou, Gaël; Molle, Virginie; Bouffartigues, Emeline; Bou, German; Shalk, Isabelle; Jouenne, Thierry; Vila‐Farrés, Xavier; Dé, Emmanuelle
Abstract : This study was undertaken to characterize functions of the outer membrane protein OmpW, which potentially contributes to the development of colistin‐ and imipenem‐resistance in Acinetobacter baumannii . Reconstitution of OmpW in artificial lipid bilayers showed that it forms small channels (23 pS in 1m KCl) and markedly interacts with iron and colistin, but not with imipenem. In vivo, 55 Fe uptake assays comparing the behaviours of Δ ompW mutant and wild‐type strains confirmed a role for OmpW in A. baumannii iron homeostasis. However, the loss of OmpW expression did not have an impact on A. baumannii susceptibilities to colistin or imipenem. Abstract :